A Remote Instructor Like Me: Student-Teacher Congruence in Online, High School Courses - Jennifer Darling-Aduana (SAGE Publishing, 2021)
Students belonging to marginalized groups experience positive impacts when taught by a teacher of the same race, ethnicity, and gender. The unique nature of standardized, asynchronous online course taking allows for greater separation of any possible educational benefits of student versus teacher-driven mechanisms contributing to these improved outcomes. Using a student-by-course fixed effect strategy on data from a large urban school district, I examined associations between whether students experienced racial/ethnic or gender congruence with their remote instructor and both engagement and learning outcomes. Students who identified as Black demonstrated higher rates of engagement, although no difference in achievement, within lessons taught by a same-race remote instructor. I find that representation is associated with engagement even when instructors follow closely scripted lessons, representation occurs in only small doses, and instruction occurs in an impersonal setting.